Caracterização genética de linhagens de Saccharomyces cerevisiae isoladas de fermentações espontâneas de cachaças de alambique da Bahia - Silva, Alice Ferreira da (2009)
The improvement in cachaça quality and increased efficiency of the production process are, necessarily, the selection of one or more appropriate yeast to the fermentation process. Saccharomyces cerevisiae is the predominant specie during the fermentation process. This study aimed to identify, genetically characterize and to analyze the genetic diversity of populations of S. cerevisiae isolated from six distilleries in the state of Bahia. The mtDNA-RFLP technique detected, among the 330 strains of S. cerevisiae, a total of 30 molecular profiles showing that the profiles were unique for each distillery. Analysis of Molecular Variance (AMOVA) found that most genetic variation is between populations of distinct distilleries, however, no significant correlation was found between geographical distance and genetic divergence of populations by the Mantel test. The STRUCTURE program identifies the six distillery share 3 gene pools supported the AMOVA and dendrogram generated from the dissimilarity of Nei e Li. The distinction of natural populations of S. cerevisiae by gene pool may reflect an adaptation to specific microhabitats. This study represents na important contribution to understanding and selection of strains, which makes this study vital to the development of strategies wich goal is the selection of strains of S. cerevisiae more adapted to fermentation of the juice of sugar cane for production of cachaça in the state of Bahia. Furthermore, the fermentation of distilleries studied may represent an important reservoir for new yeast biotypes with potential industrial applications.